Temporal Construal Effects on Abstract and Concrete Thinking Consequences for Insight and Creative Cognition. [article]. - Forster, Jens
Six studies investigate whether how distant future time perspective facilitates abstract thinking and impedes concrete thinking by altering the level at which mental representations are construed. In experiments 1 - 3 participants who envisioned their lives and imagined themselves engaging in a task 1 year later as opposed to the next day subsequently performed better on a series of insight task. In Experiments 4and 5 a distal perspective was found to improve creative generation of abstract solutions. Moreover Experiment 5 demonstrated a similar effect with temporal distance manipulated indirec , by making participants imagined their lives a year from now versus tomorrow prior to performance.In Experiment 6 distant time perspective undermined rather than enhanced analytical problem solving. -- (from the author)